2013
DOI: 10.1039/c3nr00081h
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cell imaging using multifunctional small sized KGdF4:Yb3+,Er3+ upconverting nanoparticles synthesized by a one-pot solvothermal process

Abstract: Multifunctional KGdF4:18%Yb(3+),2%Er(3+) nanoparticles with upconversion fluorescence and paramagnetism are synthesized. The average sizes of the nanoparticles capped with branched polyethyleneimine (PEI) and 6-aminocaproic acid (6AA) are ~14 and ~13 nm, respectively. Our KGdF4 host does not exhibit any phase change with the decrease of particle size, which can prevent the detrimental significant decrease in upconversion luminescence caused by this effect observed in the well-known NaYF4 host. The branched PEI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 29 publications
2
58
0
Order By: Relevance
“…HRTEM image with three rectangle zones (d1, d2, and d3) and the corresponding FFT images are shown in Figure 3D and Figure S5 −CH 2 (2881 cm −1 ), and −NH 2 (1398 cm −1 ), indicating the successful modification of −NH 2 group. 56 After being conjugated with FA, Cu x S, and PEG, the peak at 1695 cm −1 is attributed to the −CO amide stretching of the α-carboxyl group from the FA molecules, and new peak at 3463 cm −1 is assigned to −OH group because of the modification of PEG. N 2 adsorption/desorption isotherms of Y 2 O 3 :Yb/Er−Cu x S hollow spheres with different diameters are given inFigure S7A in the Supporting Information.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…HRTEM image with three rectangle zones (d1, d2, and d3) and the corresponding FFT images are shown in Figure 3D and Figure S5 −CH 2 (2881 cm −1 ), and −NH 2 (1398 cm −1 ), indicating the successful modification of −NH 2 group. 56 After being conjugated with FA, Cu x S, and PEG, the peak at 1695 cm −1 is attributed to the −CO amide stretching of the α-carboxyl group from the FA molecules, and new peak at 3463 cm −1 is assigned to −OH group because of the modification of PEG. N 2 adsorption/desorption isotherms of Y 2 O 3 :Yb/Er−Cu x S hollow spheres with different diameters are given inFigure S7A in the Supporting Information.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…For example, Wang et al reported a UCNP based uorescent biolabel for the detection of carcinoembryonic antigen. 15 However, the HPLC method also encounters some shortcomings in the sample pretreatment, such as complex process, [19][20][21][22][23][24] long detection cycle 8,25 and low sensitivity. [26][27][28][29][30][31][32] In addition, assessing the toxicity of cancer drugs to biological tissues is very important 5,[33][34][35][36][37][38] and valuable to ensure the health of humans and other creatures.…”
Section: Introductionmentioning
confidence: 99%
“…53 Compared with FMSs, HMSs have several characteristic absorptions of PEI at 2928 cm −1 , 1420 cm −1 , and 780 cm −1 , which can be assigned to the -CH asymmetric stretching vibration, -CN stretching vibration, and -NH stretching vibration in the carboxyl group, respectively. 54 The FT-IR result demonstrates that we have successfully modified the surface of the precursor by adding the PEI before generating HMSs. N 2 adsorption/desorption isotherms and the corresponding pore size distributions of LaF 3 :Ln HMSs and LaF 3 :Ln FMSs are shown in Fig.…”
Section: Resultsmentioning
confidence: 96%